Hubungan Persepsi Mahasiswa tentang Profesi Keperawatan dengan Motivasi Melanjutkan Pendidikan Profesi Ners di PSIK Universitas Jember (The Correlation of Student Perceptions About Nursing Profession with Motivation to Continuing Professional Education at - Dewa Ayu Dwi Chandra Yadnya Sari; Dodi Wijaya; Retno Purwandari (Pustaka Kesehatan, 2017)
Profession education is part of the professional education that must be passed after completingacademic education. However, there are still some students who don’t continue this professioneducation. Students perceptions about the nursing profession is one of the factors that can influencestudent’s motivation for continuing professional education. This research is aimed to analyze thecorrelation of students' perceptions about the nursing profession with the motivation of continuingnurses professional education in School of Nursing, University of Jember. This research has beenimplemented with using correlational descriptive with cross-sectional approached. The samplingtechnique used was simple random sampling, with samples in total of 97 students. Statistical test inthis research is using Chi-Square. The research’s result showed that the students who have anegative perception about the nursing profession are 52.6%. Students who have less motivation forcontinuing nurses professional education are 50.5%. The research result showed that p-value(0,003 <0.05) which means that there is a relationship between students' perceptions about thenursing profession with the motivation of continuing nurses professional education. Many factorscan affect the motivation of students, one of them is perception. Perception is a personal attributethat is generated by the cognitive abilities of a person. Perception is a crucial factor formation of thebehavior of individuals as well as student motivation for continuing nurses professional education.Recommendation of this research is socialization of nursing and professional program are neededas an earlier integral of professional education.Keywords : perception, nursing profession, motivation